2020
DOI: 10.1016/j.heliyon.2020.e05049
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of adsorption process for manganese removal in water via agricultural waste adsorbents

Abstract: Manganese has recently been a topic of interest among researchers, particularly when 1,752 million tonnes of manganese are expected to be produced by the steel industry in 2020. Manganese discharges from industrial effluents have increased manganese contamination in water sources. Its concentrations of more than 0.2 mg/L in the water sources could have negative impacts on human health and the aquatic ecosystem. Thereby, the available water treatment processes face challenges in effectively removing manganese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 89 publications
3
36
0
1
Order By: Relevance
“…The Langmuir isotherm model Adsorption isotherm provides important models in description the phenomenon of adsorption. It describes how adsorbate molecules interact with the solid phase (adsorbent) and provides explanation for the nature and mechanism of an the present study, Langmuir, Freundlich and Temkin isotherms were applied to investigate the adsorption phenomenon and was observed that all these models could be applied to describe adsorption behavior The Langmuir, Freundlich and Temkin ons are presented by the equations (3) [48], (4) [49] and (5) [33,46], respectively. The Langmuir isotherm model assumes that adsorptive of adsorbate occurs on a homogenous surface by monolayer adsorption without any interaction between the adsorbed molecules.…”
Section: Isotherm Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…The Langmuir isotherm model Adsorption isotherm provides important models in description the phenomenon of adsorption. It describes how adsorbate molecules interact with the solid phase (adsorbent) and provides explanation for the nature and mechanism of an the present study, Langmuir, Freundlich and Temkin isotherms were applied to investigate the adsorption phenomenon and was observed that all these models could be applied to describe adsorption behavior The Langmuir, Freundlich and Temkin ons are presented by the equations (3) [48], (4) [49] and (5) [33,46], respectively. The Langmuir isotherm model assumes that adsorptive of adsorbate occurs on a homogenous surface by monolayer adsorption without any interaction between the adsorbed molecules.…”
Section: Isotherm Studiesmentioning
confidence: 97%
“…However, water consumption continues to increase worldwide, followed by an increase in the generation of a large amount of liquid wastes every day, which contain hazardous materials that have harmful effects on both human and aquatic life [1][2][3][4][5][6][7][8]. Scientific studies pointed out that about 300-400 million tons of hazardous materials such as heavy metals, toxic sludge, solvents, chemicals, oil, synthetic dyes, acids and alkalis, salts, surfactants, industrial wastes and other hazardous substances are still end up into the environment every year [5]. As example, about 1200 million liters of colored wastewater resulting from textile industry are discharging every day in India [9], while 2531.67 million tons of wastewater were discharged by the mining operations in China in 2014 [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adsorbents, which are generated from natural renewable resources such as agricultural residues are becoming attracted in the treatment of the heavy metal-polluted water. These residues include rice husk ash, peanut husk, banana peels, potato peel, sugarcane bagasse, yam peel, orange peel, sunflower seed shell and tamarind fruit shell (Rudi et al, 2020).…”
Section: Inorganic Polymer and Natural Adsorbentmentioning
confidence: 99%
“…Manganese is a very toxic element which is obviously occurring in the environment, also presented as a contaminants from industrial pollution and industrial discarded [23]. Removal of Manganese is done through biological, chemical, and physical processes or by a combination of these procedures [24]. Regardless of the presence and study of physical and chemical removal processes for periods, knowledge gaps are still found.…”
Section: Introductionmentioning
confidence: 99%